The Relationship Between Loneliness and Online Sexual Behavior Community Role Players on Social Media - Afra Fairuz Alfisri; Farah Aulia (Causalita, 2024)
The increasing use of social media in Indonesia has triggered various social problems, including social media addiction. One of the growing communities is roleplayers, who use pseudo-identities to play idols or celebrities. The study analyzed the relationship between loneliness and online sex behavior in 209 roleplayers on social media. The research method used was quantitative correlation with purposive sampling, using two measuring tools, namely the Internet Sex Screening Test (ISST) by Delmonico and Miller (2003) and the UCLA Loneliness Scale Ver.3 by Russell (1996) with reliability results of 0.875 and 0.859. Data analysis using product moment correlation assisted by IBM SPSS ver. 22 for Windows which obtained the results of a positive relationship between loneliness and online sexual behavior in the roleplayer community on social media with the results of a hypothesis test with a value of r = 0.596 with a significance value of p = 0.00. This means that the higher the level of loneliness felt by the roleplayer community, the higher the tendency to behave in online sex carried out by the roleplayer community.